Preferences for Redistribution among Emigrants from a Welfare State - Panu Poutvaara; Ilpo Kauppinen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study attitudes towards income redistribution in the country of origin among emigrants from a welfare state, and those who stay there. We find a striking gender difference among Danish emigrants. Majority of men opposes increasing income redistribution in Denmark, while majority of women supports it. Also among non-migrants, women are somewhat more positive towards redistribution, but the gender difference is much smaller. We study to what extent differences in attitudes towards redistribution are driven by beliefs about the determinants of individual success, generalized trust, assimilation to the new home country, and self-selection of emigrants.
Keywords: F22; J61; D72; 330